Regulation of Posttranscriptional Modification as a Possible Therapeutic Approach for Retinal Neuroprotection - Yoko Ozawa; Toshihide Kurihara; Kazuo Tsubota; Hideyuki Okano (Journal of Ophthalmology)
Understanding pathogenesis at the molecular level is the first step toward developing new therapeutic approaches. Here, we review the molecular mechanisms of visual dysfunction in two common diseases, innate chorioretinal inflammation and diabetic retinopathy, and the role of the ubiquitin-proteasome system (UPS) in both processes. In innate chorioretinal inflammation, interleukin-6 family ligands induce STAT3 activation in photoreceptors, which causes UPS-mediated excessive degradation of the visual substance, rhodopsin. In diabetic retinopathy, angiotensin II type 1 receptor (AT1R) signaling activates ERK in the inner layers of the retina, causing UPS-mediated excessive degradation of the synaptic vesicle protein, synaptophysin. This latter effect may decrease synaptic activity, in turn adversely affecting neuronal survival. Both mechanisms involve increased UPS activity and the subsequent excessive degradation of a protein required for visual function. Finally, we review the therapeutic potential of regulating the UPS to protect tissue function, citing examples from clinical applications in other medical fields.